Analytical strategy of traditional herbal medicines : establishing chromatographic profiles of non-polar phytochemical metabolites - (:unkn) unknown (My University, 2013)
The traditional herbal medicines are widely used by African people. But their quality control is difficult, because they are complex mixtures of several herbal drugs or herbal drugs preparations. Their origin is often unknown and/or highly variable. The chromatographic profile of phytochemical metabolites is an important tool for quality assessment of these products.The objective of this work is to propose a protocol for sample preparation and liquid chromatographic and gas chromatographic profiling of non-polar metabolites for quality assessment of africain traditional herbal medicinal products.The methodology is based on the chemometric treatment of chromatographic profiles of non-polar metabolites from different batches of leaves of Combretum micranthum and Mitracarpus scaber.Metabolic profiling is carried out by non-aqueous liquid chromatography on Porous Graphitic Carbon and by high temperature gas chromatography, coupled with mass spectrometry, after extraction with dichloromethane and removal of chlorophyll adsorbed on activated charcoal.The chemometric data analysis using PLS-discriminant analysis with or without orthogonal signal correction applied to the chromatographic profiles of leaves of Combretum micranthum and Mitracarpus scaber showed small differences between batches of each herbal drug, and a clear differentiation two herbal drugs.Both analyses by liquid chromatography and gas chromatography methods detect most non-polar metabolites bioactive or/not already identified in the leaves of both species.
Keywords: African Research